Educational discourse in conflict paradigm in the light of critical analysis of discourse - Pierre Bourdieu as a model - Dhiab, Salima; Boutera, Bilel (Journal of Human Sciences, 2021)
This research document aims to monitor and analyze the contributions of educational discourse to the formation of power within societyThis study is considered descriptive, and in the context of which several methods have been used: the social inquiry, the historical method and discourse have been studied in certain texts of the book Reproduction - for a general theory in the format of l 'education, Pierre Bourdieu and Jean-Claude Pasron His choice in the method of intention samples. The researcher collected the data via the letter analysis form according to the objectives of the study. We have obtained a set of results, the most important of which are that language in the educational process is not a means of indoctrination of the sciences as much as it is a means of directing authority and hegemony which include in the social and cultural sphere